Some Observations on the use of 2-Hydroxyacetophenone Tbiosemicarbazone as a Spectrophotometric Reagent for the Determination of Vanadium(IV) and Vanadium(V). - RAMANA MURTHY, G.Y.; SREENIVASULU REDDY., T. (Asian Journal of Chemistry, 2010)
2-Hydroxyacetophenone thiosemicarbazone produce pale yellow coloured solutions with vanadium (IV) and vanadium(V) in acetic acid-sodium acetate buffer medium. The colour obtained has been used to develop spectrophotometric methods for the determination of vanadium(IV) and vanadium(V) in the concentration ranges 1.02–4.59 ppm and 0.2–4.6 ppm (λmax 360 nm) respectively.